Multi-service taphonomy. Shells, garbage, and floating palimpsests - Borrero, Luis Alberto (2014)
We discuss the importance of widening the scope of taphonomy, arguing that it is critical to study of different classes of materials within this framework. We introduce several examples related to the deposition of marine shells and garbage. In particular, we focus on debris generated by tsunamis.